Rising concerns of Mucormycosis (Zygomycosis) among COVID-19 patients; an analysis and review based on case reports in literature - Ramphul, Kamleshun; Verma, Renuka; Kumar, Nomesh; Ramphul, Yogeshwaree; Mejias, Stephanie; Lohana, Petras (Acta Biomedica Atenei Parmensis, 2021)
As the world continues to struggle with the pandemic of COVID-19 (coronavirus disease 2019), several cases of mucormycosis have been reported in these patients with a high mortality rate. We conducted a review of literature and found 19 articles with 20 patients who developed mucormycosis during their COVID-19 infection.14 (70%) were males, and 6(30%) were females. While their mean age was 52.2 ± 17.3, affected men were older than females. Ten (50%) patients also had diabetes. Common clinical findings included ophthalmologic complaints, fever, shortness of breath, and facial pain. Amphotericin B was the most common antifungal used and 40% of cases needed surgical management of the infection. Steroid use was reported in around 12 cases (60%). Unfortunately, the mortality rate was 65% in this group of patients. Several changes in care should be brought for a consistent prevention, early diagnosis, and strong management of mucormycosis in COVID-19 patients.